EVALUATION OF PRESSURE AND NON-PRESSURE FINAL IMPRESSION TECHNIQUES IN FABRICATION OF COMPLETE DENTURE - Dr. Mohammadullah (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Background: Edentulism is highly prevalent among older adults and poses significant challenges to oral function, aesthetics, and quality of life, particularly in resource-limited settings. The purpose of the study is to compare patient outcomes and denture performance using pressure versus non-pressure final impression techniques in complete denture fabrication. Aim of the study: The aim of the study was to compare patient outcomes and denture performance using pressure versus non-pressure final impression techniques in complete denture fabrication. Methods: This comparative clinical study at the Department of Prosthodontics, Bangabandhu Sheikh Mujib Medical University, in collaboration with Beau-Dent Dental, Dhaka (June 2020–July 2021), included 60 completely edentulous patients aged 50–80 years. Participants were randomly assigned to receive dentures via selective pressure (Group A) or mucostatic (Group B) impression techniques. Denture retention, stability (graded clinically), and patient comfort (VAS) were assessed at four weeks. Data were analyzed using SPSS v22 with Chi-square and t-tests; p <0.05 was considered significant. Results: Among 60 participants (mean age 65.18 ± 7.83 years; 32 males, 28 females), the pressure technique group showed better outcomes: excellent retention 18 (30.0%) vs 8 (13.3%) (p = 0.048), good stability 25 (41.7%) vs 15 (25.0%) (p = 0.015), and mean VAS comfort 82.4 ± 10.1 vs 70.3 ± 14.5 (p = 0.0004). Conclusion: Pressure final impression techniques enhance denture retention, stability, and patient comfort, making them preferable for complete denture fabrication.